The Clinical Evaluation of Periodontal Surgery with Porous Bone Graft Material (Bio-Oss (R)) and Collagen Membrane (Bio-Gide (R)) - Ohazama, Atsushi; Kitamura, Hidekazu; Suzuki, Motoyuki; Yamada, Satoru; Hasegawa, Kohji (Nihon Shishubyo Gakkai Kaishi (Journal of the Japanese Society of Periodontology), 1999)
The purpose of this study was to assess the clinical efficacy of the periodontal surgery with porous bone graft material (Bio-Oss®: BiO) and collagen membrane (Bio-Gide®: BiG). Sixtyseven adult periodontitis patients each having a Class II furcation defects or vertical defects, participated in the study. Mucoperiosteal flaps were elevated and granulation tissue in the defects were debrided with hand instruments. After each defect was filled with BiO, BiG was positioned over graft material and the defects. The flaps were replaced coronary to cover the membrane ensuring primary closure. The clinical examination were taken before surgery, at 1, 3 weeks, 3 and 6 months after surgery. Postoperatively, clinical healing generally progressed uneventfully in all patients. The significant differences were found in probing depth and clinical attachmentlevel between pre-surgery and 6 months postsurgery measurements. Mean probing depth was reduced from 6.74±1.17mm to 3.08±1.17mm with a mean reduction of 3.67±1.21mm. Mean clinical attachment level was reduced from8.39±1.99mm to 5.60±2.11mm with a mean clinical attachment gain of 2.79±1.38mm. The improvement of radioluency at defect area was noted in 48 of 66 patients. The side effects was not observed in any cases. This study revealed that the periodontal surgery with BiO and BiG is safety and clinical usefulness. J. Jpn. Soc. Periodontol., 41 : 153-165, 1999.